2006
DOI: 10.1074/jbc.m600634200
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric and Monomeric Organization of Photosystem II

Abstract: The supramolecular organization of photosystem II (PSII) was characterized in distinct domains of the thylakoid membrane, the grana core, the grana margins, the stroma lamellae, and the so-called Y100 fraction. PSII supercomplexes, PSII core dimers, PSII core monomers, PSII core monomers lacking the CP43 subunit, and PSII reaction centers were resolved and quantified by blue native PAGE, SDS-PAGE for the second dimension, and immunoanalysis of the D1 protein. Dimeric PSII (PSII supercomplexes and PSII core dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 68 publications
3
51
0
Order By: Relevance
“…1). A similar complex was reported recently during BN/SDS-PAGE separation of the stroma lamellae of spinach (3). In vivo detachment of CP43 occurs during the PSII repair cycle, whereby CP43 undergoes dephosphorylation, which in turn triggers its detachment from the PSII core (47).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…1). A similar complex was reported recently during BN/SDS-PAGE separation of the stroma lamellae of spinach (3). In vivo detachment of CP43 occurs during the PSII repair cycle, whereby CP43 undergoes dephosphorylation, which in turn triggers its detachment from the PSII core (47).…”
Section: Discussionmentioning
confidence: 81%
“…A pool of PSII, the so-called PSII␤, also present in the stroma lamellae, donates electrons to the cyclic electron flow under oxidized conditions (1). The PSII core monomers occur predominantly in the stroma lamellae (2), although a recent study showed that some dimeric PSII is also present within this region (3). Under physiological conditions, cyt b 6 f is equally distributed within the thylakoid membranes, whereas ATP synthase is localized exclusively in the unstacked stroma lamellae and within the end membranes of the grana stacks (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The damaged PSII complex enters an intricate repair cycle in which PSII is partly disassembled (8,13). The resulting interstage repair complex is presumably similar to the CP43-less PSII complex RC47, which appears during biogenesis (14). The partial disassembly allows the removal of damaged D1, which is degraded mainly by FtsH protease in cyanobacteria, whereas in plants, several Deg proteases assist this process (15)(16)(17)(18).…”
Section: Photosystem II (Psii)mentioning
confidence: 99%